#### Answer

y=$\frac{2}{3}$x+12

#### Work Step by Step

y-y$_1$=m(x-x$_1$)
y-20=$\frac{2}{3}$(x-12)
y=$\frac{2}{3}$x-8+20
y=$\frac{2}{3}$x+12

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

y=$\frac{2}{3}$x+12

y-y$_1$=m(x-x$_1$)
y-20=$\frac{2}{3}$(x-12)
y=$\frac{2}{3}$x-8+20
y=$\frac{2}{3}$x+12

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.